Criminalistic methods and means of collecting of evidentiary information for an identification (Journal of actual problems of jurisprudence, 2018)
In the present article the author considered criminalistic methods and means of collecting of evidentiary information for an identification which are made in the conditions of reality and particular persons. These traces as data carriers about the crime and its participants create for the investigator and court opportunity to establish an objective truth on concrete business.However traces of crime have to be collected, investigated and estimated in a certain order by the persons conducting criminal trial, and only after that they can be recognized by proofs. The methods stated in article and means of obtaining criminalistic information on the personality are not exhaustive. The criminalistics as the science directed on the personality has to feel constantly and tensely an impulse of the criminal environment, it always has to control it and effectively react to its changes.Key words: Traces of crime, means and methods of detection, fixing, withdrawal and preservation of various traces of crime, criminalistic odorologiya, criminalistic polygraphology, entomological examination.